2008
DOI: 10.1007/s10701-008-9216-2
|View full text |Cite
|
Sign up to set email alerts
|

On Classical and Quantum Objectivity

Abstract: Abstract. We propose a conceptual framework for understanding the relationship between observables and operators in mechanics. To do so, we introduce a postulate that establishes a correspondence between the objective properties permitting to identify physical states and the symmetry transformations that modify their gauge dependant properties. We show that the uncertainty principle results from a faithful -or equivariant -realization of this correspondence. It is a consequence of the proposed postulate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…[12]. By using the so-called momentum map formalism, we showed that the injectivity of the map between observables and operators would permit us to define physical observables as quantities that faithfully quantify the representation of abstract operators belonging to the corresponding Lie algebra g as operators acting on the space of states.…”
Section: Momenta Vs Velocitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[12]. By using the so-called momentum map formalism, we showed that the injectivity of the map between observables and operators would permit us to define physical observables as quantities that faithfully quantify the representation of abstract operators belonging to the corresponding Lie algebra g as operators acting on the space of states.…”
Section: Momenta Vs Velocitiesmentioning
confidence: 99%
“…In Ref. [12], we introduced the following terminology: the fundamental vector field v ξ ∈ T P evaluated at a point x ∈ P is said to be the representation of the abstract operator ξ ∈ g on the particular state x. A symplectic G-action is said to be Hamiltonian if there exists a map µ : g → C ∞ (P ) (called co-momentum map) such that τ •μ = ι, where τ : C ∞ (P ) → HP .…”
Section: Geometric Quantization In the Light Of The Quantum Ontomentioning
confidence: 99%
See 2 more Smart Citations
“…This article develops, in more conceptual terms, the interpretation of quantum mechanics begun in Catren [2008]. This interpretation is founded on an analysis of the symplectic formulation of mechanics (Abraham and Marsden [1978]; Libermann and Marle [1987]; Marsden and Ratiu [1999]; Souriau [1997]) and the geometric quantization formalism (Brylinski [1993]; Kostant [1970]; Souriau [1997]; Woodhouse [1992]).…”
Section: Introductionmentioning
confidence: 99%